Rejection Sensitivity and Attachment Avoidance as Predictors of Intimacy Struggles in Romantic Relationships - Batthyany, Karina; Hernández, Carlos (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate whether rejection sensitivity and attachment avoidance significantly predict intimacy struggles in romantic relationships.Methods and Materials: A correlational descriptive research design was employed using a sample of 433 adults from Mexico, selected based on the Morgan and Krejcie sample size table. Participants completed standardized self-report measures assessing rejection sensitivity, attachment avoidance, and intimacy struggles. Data were analyzed using SPSS-27, including Pearson correlation to examine the relationships between the dependent variable and each independent variable, and multiple linear regression to assess the predictive power of the independent variables on intimacy struggles. All statistical assumptions were checked and met before performing the analyses.Findings: Results indicated significant positive correlations between intimacy struggles and both rejection sensitivity (r = .51, p < .01) and attachment avoidance (r = .46, p < .01). Multiple regression analysis revealed that rejection sensitivity (β = .39, t = 7.75, p < .01) and attachment avoidance (β = .33, t = 7.31, p < .01) were both significant predictors of intimacy struggles. The overall model was statistically significant, F(2, 430) = 105.89, p < .01, with an R² of .33, indicating that 33% of the variance in intimacy struggles was explained by the predictor variables.Conclusion: The findings highlight that both rejection sensitivity and attachment avoidance are key psychological factors contributing to intimacy struggles in romantic relationships. These results underscore the importance of addressing underlying emotional vulnerabilities in relationship counseling and psychological interventions, particularly in culturally diverse populations such as adults in Mexico.